DESIGNING ICON-MODULE TO SUPPORT WRITING ABILITY IN WRITING DESCRIPTIVE TEXT BASED ON CONTEXTUAL APPROACH - Anggara, Edo; ., Ikhsanudin; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The focus of this research is to design the construct of ICON-Module based on contextual approach for teaching descriptive text. This research was conducted on the seventh grade students of SMP Mujahidin Pontianak. The method of this research is development research which consist of four phases; analysis, design, develop, and implement. This material was designed as supplementary material to support writing ability in describing places. The respondents in this research are the seventh grade students, English teacher at SMP Mujahidin Pontianak, two Eight semester students of Tanjungpura University and four students as the independent learner. In this research, the researcher found that ICON-Module can support writing ability in describing places for seventh grade students of SMP Mujahidin Pontianak. It can be seen from the result of implementation phase when the researcher tried out the product to see the usability of the ICON- Module. The result of the questionnaire in implement phase is 83.93, it showed that the ICON-Module is usable to be used by students as the supplementary material to support students writing ability in describing places. Key words: Development Research, ICON-Module, Designing Material, Contextual approach. Â  Abstrak: Fokus penelitian ini adalah untuk merancang ICON-Module berdasarkan pendekatan kontekstual untuk mengajar deskriptif teks. Penelitian ini dilakukan pada siswa kelas VII SMP Mujahidin Pontianak. Metode penelitian ini adalah penelitian pengembangan yang terdiri dari empat tahap; analisis, desain, mengembangkan, dan implementasi. Bahan ini dirancang sebagai bahan tambahan untuk mendukung kemampuan menulis dalam menggambarkan tempat. Responden dalam penelitian ini adalah siswa kelas tujuh, guru Bahasa Inggris di SMP Mujahidin Pontianak, dua mahasiswa semester delapan universits Tanjungpura dan empat siswa sebagai pembelajar independen. Dalam penelitian ini, peneliti menemukan bahwa ICON-Module dapat mendukung kemampuan menulis dalam mendeskripsikan tempat untuk siswa kelas tujuh SMP Mujahidin Pontianak. Hal itu dapat dilihat pada hasil tahap implementasi ketika peneliti mencoba produk untuk melihat kegunaan dari ICON-Module. Hasil kuesioner di tahap implementasi adalah 83,93, itu menunjukkan bahwa ICON-Module ini dapat digunakan oleh siswa sebagai bahan tambahan untuk mendukung kemampuan siswa menulis dalam menggambarkan tempat. Kata Kunci: Penelitian Pengembangan, ICON-Module, Merancang Materi, Pendekatan Kontekstual.